Enhancing the efficiency of bortezomib conjugated to pegylated gold nanoparticles: an in vitro study on human pancreatic cancer cells and adenocarcinoma human lung alveolar basal epithelial cells. (2nd August 2016) - Coelho, Sílvia Castro; Almeida, Gabriela M.; Santos-Silva, Filipe; Pereira, Maria Carmo; Coelho, Manuel A. N.
ABSTRACT: Objectives : Gold nanoparticles have become promising vectors for cancer diagnosis and treatment. The present study investigates the effect of bortezomib (BTZ), a proteasome inhibitor, conjugated with pegylated gold nanoparticles (PEGAuNPs) in pancreatic and lung cancer cells. Methods : Synthesized gold nanoparticles (PEGAuNPs) were conjugated with bortezomib antitumor drug. We investigated the cytotoxicity induced by BTZ conjugated with functionalized gold nanoparticles in vitro, in the human pancreatic (S2-013) and lung (A549) cancer cell lines. Results : We found an efficient of conjugation of BTZ with PEGAuNPs. In vitro assays showed that after 72 h' incubation with PEGAuNPs-BTZ cancer cells revealed alterations in morphology; also for S2-013 and A549 cancer cells, the IC50 value of free BTZ is respectively 1.5 and 4.3 times higher than the IC50 value of PEGAuNPs-BTZ. Furthermore, for TERT-HPNE, the IC50 value is around 63 times lower for free BTZ than the conjugated nanovehicle. Cell growth inhibition results showed a remarkable enhancement in the effect of BTZ when conjugated with AuNPs. Conclusions : Our findings showed that conjugation with PEGAuNPs enhance the BTZ growth-inhibition effect on human cancer cells (S2-013 and A549) and decreases its toxicity against normal cells (TERT-HPNE).